Cytokine levels in gingival crevicular fluid samples of patients wearing clear aligners - Sana Bint Aziz; Gurkeerat Singh (Elsevier, 2020)
Objective: The aim of this study was to assess & compare the changes in cytokine levels in GCF samples of patients wearing clear aligners. Methods: GCF samples of 10 patients undergoing orthodontic treatment, for correction of lower anterior crowding with clear aligners, were collected on day 0, 1, 3, 7 and 21 using periopaper strips. The upper arch was taken as the control site. The samples collected were further analyzed using commercially available ELISA based kits. Results: The mean levels of IL-1β at day 0, 1, 3, 7 and 21 were compared between experimental and control sites using unpaired t-test and it was found that the levels of IL-1β were significantly elevated on experimental site in comparison to control site. Conclusion: It was concluded from the study that elevation in levels of IL-1β as a biomarker of orthodontic tooth movement reaches its peak after 24 h of force application. The clear aligners, as an alternative to conventional fixed orthodontic treatment, were found to be efficient in correcting mild to moderate lower arch crowding.